On the Origins of the Demographic Transition. Rethinking the European Marriage Pattern - Faustine Perrin (European Historical Economics Society (EHES), 2020)
Why did France experience the demographic transition first? This question remains one of the greatest puzzles of economics, demography, and economic history. The French pattern is hard to reconcile with elucidations of the process as found in other countries. The present analysis goes back to the roots of the process and offers novel ways of explaining why people started to control their fertility in France and how they did so. In this paper, I track the evolution of marriage patterns to a point before the premises of the demographic transition. I identify three distinct phases. Next, I rely on exploratory methods to classify French counties based on their discriminatory features. Five profiles emerge. I discuss these profiles through the lens of the French Revolution, one of the greatest events that ever occurred in French history, which irretrievably altered its society. In particular, the results show that the fertility transition was not as linear, but more complex than previous research had argued. They show the importance of accounting for cultural factors and for individuals' predispositions to adapt more or less quickly to societal changes. Yet cultural factors are not all. They can help to explain the timing of the transition and the choice of methods used to control fertility, but modernity and gender equality are also needed to describe the mechanisms in play behind the process.
Keywords: J12; J13; J16; N33; O15; O18; Z12; 330; Demographic Transition; European Marriage Pattern; French Revolution; Gender Equality; Women Empowerment